2016
DOI: 10.3892/ijo.2016.3557
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin enhances the anticancer activity of NVP-BEZ235 against neuroblastoma cells in vitro and in vivo through autophagy

Abstract: Abstract. The aberrant activation of PI3K/Akt/mTOR signaling pathway plays an important role in the oncogenesis, prognosis and chemotherapy resistance of neuroblastoma. However, NVP-BEZ235, a potent dual PI3K and mTOR inhibitor have not shown beneficial effects on neuroblastoma especially in terms of apoptosis induction as a single agent. We therefore attempted to explore an effective combination regimen to enhance the anticancer activity of NVP-BEZ235. Interestingly, we found that oridonin, a natural biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Hara [543]. As an orally available drug, oridonin is demonstrated to have anti-cancer activities in multiple cancers over the past decades, including leukemia, lymphoma, osteosarcoma, myeloma, uveal melanoma, neuroblastoma, hepatocellular, laryngeal, esophageal, and oral squamous cell carcinoma, lung, colorectal, breast, gastric, pancreatic, and prostatic cancers [543][544][545][546][547][548][549][550][551][552][553][554][555][556][557][558]. The anti-cancer effects of oridonin are shown in many aspects, including the induction of cell apoptosis, autophagy, cell cycle arrest, and the suppression of angiogenesis, cell migration, invasion and adhesion [554,[559][560][561][562][563][564].…”
Section: Oridoninmentioning
confidence: 99%
See 2 more Smart Citations
“…Hara [543]. As an orally available drug, oridonin is demonstrated to have anti-cancer activities in multiple cancers over the past decades, including leukemia, lymphoma, osteosarcoma, myeloma, uveal melanoma, neuroblastoma, hepatocellular, laryngeal, esophageal, and oral squamous cell carcinoma, lung, colorectal, breast, gastric, pancreatic, and prostatic cancers [543][544][545][546][547][548][549][550][551][552][553][554][555][556][557][558]. The anti-cancer effects of oridonin are shown in many aspects, including the induction of cell apoptosis, autophagy, cell cycle arrest, and the suppression of angiogenesis, cell migration, invasion and adhesion [554,[559][560][561][562][563][564].…”
Section: Oridoninmentioning
confidence: 99%
“…Oridonin is also shown to induce autophagy in many cancer cells, which is associated positively or negatively with apoptosis. It induces autophagy to mediate apoptosis in human NSCLC A549 and neuroblastoma SHSY-5Y cells [558,568]. On the other hand, autophagy provides a protective role against oridonin-induced apoptosis, as autophagy inhibitor enhances oridonin-induced apoptosis in human cervical carcinoma HeLa, multiple myeloma RPMI 8266, laryngeal cancer HEp-2 and Tu212, and epidermoid carcinoma A-431 cells [569][570][571][572].…”
Section: Oridoninmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,12 Oridonin is a kind of active diterpenoid derived from traditional Chinese medicine. 13 It has a wide range of biological effects, such as anticancer, antibacterial, and anti-inflammatory activities. 14 And, many oridonin derivatives have been designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that oridonin enhances the anticancer activity of NVP-BEZ235 against NB cells through autophagy. 13 And, it has also been proved that oridonin can also generate ROS to sensitize NB cells to TRAILinduced apoptosis. 26 At present, we investigate the effects of oridonin on NB cells and further explore the detailed molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%